تأثير استخدام تكنولوجيا المعلومات على الحصّة السّوقيّة في المصارف التجاريّة السّوريّة (دراسة ميدانيّة في المصارف التّجارية العامّة والخاصّة) - مرهج, منذر; معلا, رهام (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The research aimed to identifying the relationship between the use of information technology and enhance of market share in Syrian commercial Banks . By identifying the extent of the impact of each dimensions of information technology, by determining the extent to which both the information technology dimensions and the basic requirements of the application of information technology affect market share, the researchers relied on the prescriptive approach and the descriptive approach as a general approach to research, the questionnaire was distributed to 250 senior management in public and private commercial banks, and this study concluded several results, the most important of which was a moral relationship between the use of information technology and the market share, and this relationship is acceptable and positive, and is due to the lack of human resource skills and modern material components, especially in senior management, the researchers have reviewed many important results and made several suggestions and recommendations, the most important of which was the need to develop an appropriate strategy for the use of information technology supporting its operations within the overall strategy of the bank and following up on its implementation and evaluation in order to achieve the basic objectives of the Bank. هدف البحث إلى التعّرف على العلاقة بين استخدام تكنولوجيا المعلومات وتعزيز الحصّة السّوقيّة في المصارف التّجاريّة السّوريّة، من خلال تحديد مدى تأثير كل من أبعاد تكنولوجيا المعلومات والمتطلبات الأساسيّة لتطبيق تكنولوجيا المعلومات، على الحصّة السوقيّة، وقد اعتمد الباحثان على المقاربة الاستنباطية وعلى المنهج الوصفيّ كمنهج عام للبحث، وقام الباحثان بتوزيع استبيان على(250) فرداً من الإدارة العليا في المصارف التّجاريّة العامّة والخاصّة، وقد خلصت هذه الدّراسة إلى عدّة نتائج، كان أهمها وجود علاقة مباشرة بين استخدام تكنولوجيا المعلومات والحصّة السّوقيّة، وهذه العلاقة مقبولة وموجبة، ويعود السبب في ذلك إلى ضعف وجود مهارات موارد بشرية ومكونات ماديّة حديثة، وخاصةً في الإدارة العليا، كما قدّم الباحثان العديد من المقترحات والتوصيات، والّتي كان أهمها ضرورة وضع إستراتيجية مناسبة لاستخدام تكنولوجيا المعلومـات الدّاعمـة لعملياتها في إطار الإستراتيجية العامة للمصرف، ومتابعة تنفيذها وتقييمها بما يحقق الأهـداف الأساسـية للمصرف.